2020
DOI: 10.4103/ijcm.ijcm_231_19
|View full text |Cite
|
Sign up to set email alerts
|

Stress and coping strategies among undergraduate nursing students: A descriptive assessment from Western Rajasthan

Abstract: Background: Nursing is a very challenging profession, which requires very stringent training since initial years of nursing education. Throughout the training period, students are exposed to various stressful situations. Inability to cope up with varied stressors may lead to psychological distress and impede students' pursuits of nursing career. Objectives: The aim of the present study is to assess stress and coping strategies among nursing students of Western Rajasthan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
23
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 11 publications
7
23
2
5
Order By: Relevance
“…The study participants adopted mostly positive coping strategies such as prayer/meditation, active coping, help from others, positive reframing, etc and the least, the negative strategies such as self-blame, venting, drug abuse, etc. This finding corroborates with the findings of Singh, Nebhiani, Dhar and Kumar et al 11,12,22,23…”
Section: A Little Bit N (%)supporting
confidence: 93%
See 2 more Smart Citations
“…The study participants adopted mostly positive coping strategies such as prayer/meditation, active coping, help from others, positive reframing, etc and the least, the negative strategies such as self-blame, venting, drug abuse, etc. This finding corroborates with the findings of Singh, Nebhiani, Dhar and Kumar et al 11,12,22,23…”
Section: A Little Bit N (%)supporting
confidence: 93%
“…The findings were much lower in comparison to study conducted by Singh, Nebhinani, Dhar, Kumar. 11,12,22,23 The percentage of stress finding was higher than the findings of the study carried out by Cheung (20.0%) in undergraduate nursing students, Maharaj (41.2%) among working nurses. 20,21 The study also revealed academic year of the student as one of the correlates of depression.…”
Section: A Little Bit N (%)contrasting
confidence: 58%
See 1 more Smart Citation
“…This finding is similar to a study done among undergraduate nursing students in Western Rajasthan. 16 As the lockdown and the emergence of cases were similar in India and Nepal with similar culture and methods of teaching too, the results were found to be consistent. These findings are also in consistent with other study done in Jimma University in Ethiopia which reported the use of healthy coping strategies as the common method of coping.…”
Section: Discussionsupporting
confidence: 52%
“…Key stressors included interface concerns, the academic load, the attitude of other professionals toward nursing, a lack of free time, and a fear of examinations. 3 In a study of nursing students in Brazil, most participants presented low levels of stress during general course activities. Their main stressor was a lack of time for leisure, family, and extracurricular activities.…”
Section: Introductionmentioning
confidence: 99%